(untitled) (Anclajes, 2026)
Writers with a critical perspective offer insights into issues that are vital for a community to address as it strives for a more harmonious being. In this interview, Ana María Shua (Buenos Aires, 1951) summarizes and traces her diverse literary output (for children, young adult, and adult audiences) and explores the evolution of her poetics, from her early years to literary maturity. The author establishes a constant dialogue between history and literary craft, particularly regarding contexts that were often hostile to aesthetic creation. Her biography intersects with the bleak conditions for literary production from the 1970s and early 1980s until the return of democracy. She reveals the hidden side of the creative process and the specificities of each literary genre, a learning experience that she chronicles and illustrates with concrete examples.